TLR ligands as immunomodulators: mechanistic insights and therapeutic potential in infectious and inflammatory diseases - Divya Verma; Sarthak Dhar; Takhellambam Malemnganba; Sanyukta Sharma; Sramona Kar; Vijay Kumar Prajapati (Molecular Biology Reports, 2026)

District-Level Groundnut Yield Prediction in Gujarat State Using Machine Learning and Remote Sensing Data - Drashti Nayakpara; Divya Prajapati; Kamal Pandey; N. R. Patel (Journal of the Indian Society of Remote Sensing, 2026)

Identifying Potential Locations of Hydrologic Monitoring Stations Based on Topographical and Hydrological Information - Akshay Singhal; Muhammed Jaseem; Divya; Shiblu Sarker; Pragati Prajapati; Ankit Singh; Sanjeev K. Jha (Water Resources Management, 2024)

Chromomycin, an antibiotic produced by Streptomyces flaviscleroticus might play a role in the resistance to oxidative stress and is essential for viability in stationary phase - Divya Prajapati; Namita Kumari; Keyur Dave; Vaidehi Chatupale; Jayashree Pohnerkar (Environmental Microbiology, 2019)
Summary The well‐known role of antibiotics in killing sensitive organisms has been challenged by the effects they exert at subinhibitory concentrations. Unfortunately, there are very few published reports on the advantages these molecules may confer to their producers. This study describes the construction of a genetically verified deletion mutant of Streptomyces flaviscleroticus unable to synthesize chromomycin. This mutant was characterized by a rapid loss of viability in stationary phase that was correlated with high oxidative stress and altered antioxidant defences. Altered levels of key metabolites in the mutant signalled a redistribution of the glycolytic flux toward the PPP to generate NADPH to fight oxidative stress as well as reduction of ATP‐phosphofructokinase and Krebs cycle enzymes activities. These changes were correlated with a shift in the preference for carbon utilization from glucose to amino acids. Remarkably, chromomycin at subinhibitory concentration increased longevity of the non‐producer and restored most of the phenotypic features’ characteristic of the wild type strain. Altogether these observations suggest that chromomycin may have antioxidant properties that would explain, at least in part, some of the phenotypes of the mutant. Our observations warrant reconsideration of the secondary metabolite definition and raise the possibility of crucial roles for their producers.